Tata Kelola Sains Level Mikro di Lembaga Pendidikan Islam - Alfiyah Luthfiyana; Irawan Irawan; Tedi Priatna (Jurnal Dirosah Islamiyah, 2023)
Every educational institution must have goals that must be achieved. If these goals have been achieved, then the school will feel that the efforts that have been made are not in vain. Therefore, every school tries as much as possible to implement all methods to achieve it. One of these methods is to keep up with the times. The more advanced the development of the current era, the learning methods are also more advanced. Many of the schools use a variety of sophisticated technologies. Therefore, this research appears to solve the problems that the average school is experiencing. Therefore, this study aims to find out what is meant by the inquiry method and what effect it has if the inquiry method is applied to educational institutions. The method used in this study is a descriptive qualitative approach to the field study method. With the results of the research, MTS Al-Kautsar teachers have taught directly and provided material through videos sent via the whatsapp group. Fill in the video about food experiments which will later be tried directly by the students. The usefulness of the video is so that students understand better before conducting experiments. So from this example, the school already uses the inquiry method. Furthermore, if it is concluded, science learning at MTS Al-Kautsar does not require students to actively ask questions. Indeed, the school has used the method in accordance with the times at this time. But if there are students who are still embarrassed to ask when they feel they don't understand, then the teacher has not fully implemented the inquiry method. Therefore, there are still many students who don't like science learning and many still forget the theories or formulas that have been taught. Keywords: Science, Education, Inquiry